Relationship between principals digital leadership and teachers digital competency in Klang district secondary schools - Abdullah, Nurul Salwani; Abdul Kadir, Suhaida (Association for Researcher of Skills and Vocational Training, 2024)
Malaysia Education Blueprint (MEB, 2013-2025) provides comprehensive plan for sustainable transformation of Malaysia education to equip students for the future world scenario. In its seventh shift, leveraging ICT to scale up quality learning across Malaysia and developing globally competent youths has taken place in Malaysian schools in three waves since 2013 until 2025 (Ministry of Education, 2013). Simultaneously, the Covid19 pandemic has reduced the chances of conducting lessons in a traditional classroom setting. Due to this, formal school institutions are forced to adopt digital learning as a new platform for teaching and learning. Consequently, teachers and principals are required to be well versed and competent in the digital technology as they are forced to master digital teaching skills within a short time span. Schools have to equip the students with all the knowledge and skills necessary to survive in the era of “Internet of Things” and Artificial Intelligence. Teachers need to be digitally literate and inevitably the responsibility of bringing about change and preparing teachers and the school environment for IR 4.0 job market lies on the shoulders of the school principals. Nonetheless, both teachers and principals were unprepared to embrace the digital changes in the current educational scenario. This research explored the relationship between principals’ digital leadership and teachers’ digital competency in Klang district secondary schools. 354 respondents from 39 secondary schools participated in this research. Based on the data analysed that there is a significant positive relationship at a moderate level between the principals’ digital leadership and the teachers’ digital competency with a value of r =0.41 and p = .00 (p <0.05). It can be concluded that when principals’ digital leadership is a moderate level, teachers’ digital competency is also at a moderate level. In order to further enhance this digital leadership and teachers’ digital competency, Ministry of Education, State Education Department (JPN) and District Education Office (PPD) must indeed take the initiative to provide ample training and knowledge related to digital leadership in order to better equip principals to lead schools.